The Role of Bhakti Wira Tamtama Hospital Semarang in Covid-19 Prevention and Control - Jarwa Jarwa; Endang Wahyati Yustina; Inge Hartini (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: Based on Law Number 44 of 2009 concerning Hospitals, it is stated that the Hospital is a health service institution for the community. Hospital is part of the health care system, has a very strategic role in improving the health status of the community. Complete health services are needed during the Covid-19 pandemic. Hospitals are required to provide services in accordance with the standards of the World Health Organization (WHO). WHO in 2020 declared Covid-19 a global pandemic. Indonesia is also affected by the pandemic. The pandemic y has directly caused major changes in Hospital services. This includes the Bhakti Wira Tamtama Hospital in Semarang, which is an Army Hospital under the Military Command.The purpose of this study was to obtain an overview of the regulation and implementation of the roles and factors that influence the prevention and control of Covid-19. The research method used is qualitative research. Primary data was taken from direct interviews with sources, namely the task force Covid, management and patients and their families. The method of analysis using qualitative data analysis.Research result. The Bhakti Wira Tamtama Hospital has a Covid-19 alert status. Handling began at the start of the pandemic. 112 regular beds and 4 ICU beds were prepared from a total of 187 beds for the isolation of Covid-19 patients and 63 of the 332 health workers were prepared for the handling and prevention of Covid-19. The role of the Bhakti Wira Tamtama Hospital in dealing with the Covid-19 outbreak is in accordance with the Outbreak Law, Health Quarantine Law, Health Law, Hospital Law, Presidential Decree No. 11 of 2020, the Governor of Central Java's Decree, namely to participate in overcoming the outbreak starting from from screening, patient care, education to the return of the bodies of Covid-19 patients. The purpose of setting the role is to carry out Health Quarantine in accordance with the Health Quarantine Act. The mechanism for implementing its role is in accordance with and in line with regulations from the Central and Regional Governments. The hospital team consists of the screening, education, laboratory, nursing, disinfection and corpse recovery teams. The form of the role can be in the form of imperative and facultative roles. The influencing factors when viewed from juridical factors are in accordance with existing laws and regulations, social factors by dismissing the notion of